Some properties of the Isolated Cortex of the Medaka (Oryzias Latipes) egg as elucidated by scanning electron microscopy - Formacion, Minda (1983)
The effects of Ca²⁺, pH, ATP and Plase A₂ on the release of the cortical alveoli (CA) and the morphological changes in the microvilli of isolated egg cortices of Oryzias latipes were studied with the scanning electron microscope. Ca release from the isolated egg cortices of the medaka was observed at the threshold level of 1 mM Ca² at pH 6.7 in the ACA medium, which on addition of PLase A₂ was lowered to 50 µM Ca²⁺. ATP at 1 mM and 10 mM lowered further the threshold level to 1 µM Ca²⁺. The response of the isolated coritces to PLase A₂ was not enhanced with 1 mM ATP but with 10 mM ATP, the threshold level was reduced to 1 µM Ca²⁺. Prominent modifications of the microvilli were observed with the addition of ATP and PLase A₂ to the ACA medium; e.g., enlargement, branching, elongation, and formation of lobed tips. Granules (diameters ranging from 0.25-0.60 µM) were noted on the surface of the intact CA of cortices, the surface of which was mechanically removed, and isolated in Ca-free ACA medium. A schematic diagram of the process of CA release in the isolated cortices was proposed, and the view is presented that the granules on the surface of the CA are gradually dissolved in the process of exocytosis which may be related to the enzymatic dissolution of the CA envelop during release. The possible role of ATP in the release of CA was discussed.
Thesis (Master of Science). -- Diliman, Quezon City : UP-CAS, May 1983.